From the Guest Editors - Urszula Ledzewicz; Andrzej Swierniak (Mathematical Biosciences and Engineering)
The idea for this volume came from the session ''Control and Dynamics ofBiomedical Systems,'' which we organized at the Fourth World Congress of NonlinearAnalysts held in Orlando, Florida, on June 30–July 7, 2004. We inviteda number of speakers, and although not all could attend and give a talk in person,many expressed interest in contributing a paper. Following an invitation fromYang Kuang to put together a volume on the topic as a special issue of MathematicalBiosciences and Engineering, some papers presented at the session weresubmitted immediately, and others were contributed after the Congress.For the full paper, please click the 'Full Text' button above.